Integrated Modeling Driven Evaluation of Opportunities for Climate‐Resilient Perennial Biomass Crop Plantings in Flood‐Prone Agricultural Landscapes - Ganesh R. Ghimire; Yan Liu; Esther Parish; Sudershan Gangrade; Shih‐Chieh Kao; Christopher DeRolph; Karen Maguire; Henriette Jager (Journal of Flood Risk Management, 2025)
ABSTRACT Adapting to future climate change in flood‐prone landscapes will require climate‐resilient agricultural systems. Planting perennial crops, like switchgrass and willow, along river corridors can mitigate future flooding while supporting bioenergy markets. We developed an integrated assessment linking climate, hydrologic, and inundation model results to assess future flood risk to river‐adjacent agricultural lands in the Mid‐Atlantic Region (MAR) and explore this opportunity. We produced ensemble streamflow projections for every MAR stream using a hydrologic model driven by a suite of downscaled and bias‐corrected Coupled Model Intercomparison Project Phase 6 climate projections. We then conducted high‐resolution inundation mapping based on projected flood frequencies for baseline and future periods. Results show that in the near‐term future, at least two‐thirds of the streams will experience 100‐year floods more severe than the baseline 200‐year floods. Riparian zones are projected to face a median rise of inundation by 9.5%–24.1%. Results show that there is an opportunity to mitigate flooding in over half of MAR's counties with the quantities of switchgrass and willow plantings anticipated for mature bioenergy markets, even under the most extreme (200‐year) flood events. Our integrated modeling framework can guide similar regions to evaluate opportunities for flood‐resilient agricultural systems under climate change.